Impact of Plai-Zampen programs on librarians' professional development for technological advancement and management - A. Asid, Benhur (Edelweiss Applied Science and Technology, 2024)
The purpose of this study is to assess the impact of the programs initiated by the Philippine Librarians Association, Inc.- Zamboanga Peninsula (PLAI-ZamPen) for the last 5 years on Librarians’ Professional Development for Technological Advancement and Management. It highlights librarians' adaptation to technological demands, emphasizing skills in software, systems, and data analysis. Employing a quantitative research design with a descriptive survey method, the study utilizes 86 librarian respondents to evaluate its profiles, program impact, and effectiveness variations based on library types, membership duration, and roles. Using tools like the Kruskal-Wallis H Test and Weighted Mean, the study provides a comprehensive analysis, emphasizing the importance of ongoing professional development for libraries to remain relevant and responsive in hybrid learning environments. The findings revealed a significant positive impact, with programs effectively equipping librarians with essential skills and fostering a culture of innovation. The analysis of membership demographics highlights a predominance of academic librarians and a mix of experienced and novice members, underscoring the inclusivity and effectiveness of PLAI-ZamPen's initiatives. In conclusion, this study affirms that the programs initiated by PLAI-ZamPen significantly enhance librarians' professional development, particularly in the realms of technological advancement and management. The positive impact of the programs extends beyond individual skill enhancement; it also bolsters libraries' abilities to adapt to evolving community needs, thereby ensuring continued relevance and excellence in service delivery. It is recommended that continued innovation and expansion of professional development programs, focusing on emerging technological trends and management strategies be considered. Thus, it will enhance librarians' proficiency in digital tools and foster global collaboration, ensuring that libraries remain essential hubs of knowledge and service excellence.